Isolation of quinolone alkaloid with potential anti-diabetic activity from Abroma Augustum (L.) L.F (Bangladesh Journal of Botany, 2025)
A chemical and biological investigation on Abroma augustum (Malvaceae) led to the isolation of a new alkaloid, 3-methoxy-4(1H)-quinolone (1), along with three known compounds: 4-methoxy cinnamic acid (2), taraxerol (3), and stigmasterol (4). Molecular docking studies revealed their varying binding affinities toward diabetes-related receptors.  The methanol extract was partitioned into hexane (HSF), chloroform (CSF), ethyl acetate (EASF), and aqueous (AQSF) fractions, which were evaluated for antidiabetic, cytotoxic, thrombolytic, and antioxidant activities. In alloxan-induced rats, HSF, CSF, and EASF significantly reduced blood glucose up to 69%. HSF showed moderate cytotoxicity (LC50: 23.496 μg/ml), while EASF exhibited notable thrombolytic (27.77%) and strong antioxidant activity (IC50: 5.61 μg/ml), surpassing standard BHT (IC50: 14.57 μg/ml). These findings highlight the plant's medicinal potential, warranting further investigation.Bangladesh J. Bot. 54(3): 593-599, 2025 (September)